Combined effect of temperature and ammonium addition on fermentation profile and volatile aroma composition of Torrontés Riojano wines - Perez, Maria Dolores; Assof, Mariela Vanesa; Bolcato, Esteban Augusto; Sari, Santiago Eduardo; Fanzone, Martín Leandro (2018)
The effects of process temperature and ammonium supplementation on fermentation profile, volatile aroma composition and wine sensory characteristics were evaluated in Torrontés Riojano (Vitis vinifera L.) wines from Mendoza (Argentina). To do so, musts were fermented at two different temperatures (14 y 22 °C), with and without addition of 200 mg/L of yeast assimilable nitrogen, using ammonium salt. The fermentation profile was obtained by daily monitoring weight loss and counting viable yeasts. HS-SPME-GC-MS procedure was applied in order to determine the aromatic profile of wines. Two-way ANOVA and PCA analysis revealed that the treatment fermented at low temperature and with nutrition (14AN) showed the maximal concentration of terpenes and lower levels of pH and volatile acidity, obtaining a better quality wines. However, the treatment fermented at higher temperature and with nutrition (22AN) was identified by the sensory panel as the most aromatic wine, finding notes of pineapple and banana related with its greater amounts of higher alcohol acetates. Low temperature displayed slow fermentations and the nitrogen salts were hardly consumed by yeast in this process condition. Ammonium addition and high temperature increased the maximal fermentation rate producing shorter fermentation times and greater amounts of higher alcohols acetates.